COGNITIVE APPROACH TO LITERATURE EDUCATION: MEMORY, THINKING AND COGNITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the development of literature education, creativity in students, thinking in the development of visual potential, the formation of scientific knowledge and views on the perception of the artistic text.